State policy of the republic of kazakhstan in the field of prevention of juvenile delinquency (Journal of actual problems of jurisprudence, 2020)
One of the need bearings of the state social approach is to guarantee compliance with the rights of the child cherished within the Structure of the Republic of Kazakhstan, universal settlements and other standardizing lawful acts. The concept of lawful arrangement of the Republic of Kazakhstan for the period from 2010 to 2020, in Admirable 24 of 2009, No. 858, offers arrangements to a number of complex issues, counting moving forward the framework of measures to anticipate wrongdoing among minors. Right now, the avoidance of adolescent misconduct is respected by the universal community as one of the most regions of the battle against wrongdoing. The issue of adolescent wrongdoing in Kazakhstan, in spite of the endeavors of a huge number of administrations, remains one of the foremost troublesome to illuminate. Anticipation is carried out by state and open organizations of different sorts. Among them, an critical part is played by the inside Undertakings bodies, which incorporate specialized divisions in this line of work. Work goes continually in this heading. Each state is inquisitive about guaranteeing that each child, each young person, develops up to be a genuine individual and a commendable citizen of their nation. The criminal policy of the state decides the most bearings and shapes of wrongdoing control, standards, strategies, errands and substance of the exercises of state bodies authorized to combat criminal encroachment. Criminal legislative issues pointed at securing the person, the sacred rights and flexibilities of citizen, management order, equity, peace and security of mankind. Subsequently, the proper arrangement of criminal approach is one of the measures against wrongdoing, contributes to the solidness of the state and the arrangement of gracious society. It decides the substance of criminal enactment, in settling issues of criminal obligation, introduce the objectives, framework and sorts of criminal punishments, the plausibility and grounds for exception from discipline, as well as issues of moving forward the framework of measures to anticipate adolescent wrongdoing. This can be not coincidental, since at show the avoidance of adolescent misconduct is respected by the worldwide community as one of the most headings of the battle against crime. Key words: state policy, juvenile delinquency, prevention, crime prevention, juvenile crime control.